2022
DOI: 10.3390/biomedicines10102580
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Antimicrobial Coatings and Material Modification Strategies for Preventing Urinary Catheter-Associated Complications

Abstract: In recent years, we have witnessed prominent improvements in urinary catheter coatings to tackle the commonly occurring catheter-associated urinary tract infection (CAUTI) in catheterized patients. CAUTIs are claimed to be one of the most frequent nosocomial infections that can lead to various complications, from catheter encrustation to severe septicaemia and pyelonephritis. Besides general prevention hygienic strategies, antimicrobial-coated urinary catheters show great potential in the prevention of urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 127 publications
0
12
0
Order By: Relevance
“…The use of hydrogels, polytetrafluoroethylene (PTFE), polyethylene glycol (PEG), polyzwitterions, and specific enzymes as coatings all involve material modifications. As antimicrobial coatings, apart from various antibiotics (chosen for specific infecting agents), metallic ions, nanoparticles, nitric oxide bacteriophages, and antimicrobial peptides (AMPs) may be used in order to prevent biofilm formation [ 36 ]. Although there are numerous data from in vivo, in vitro, and clinical studies, a unanimous conclusion on which coating is the right choice for a specific pathogen has not been reached.…”
Section: Discussionmentioning
confidence: 99%
“…The use of hydrogels, polytetrafluoroethylene (PTFE), polyethylene glycol (PEG), polyzwitterions, and specific enzymes as coatings all involve material modifications. As antimicrobial coatings, apart from various antibiotics (chosen for specific infecting agents), metallic ions, nanoparticles, nitric oxide bacteriophages, and antimicrobial peptides (AMPs) may be used in order to prevent biofilm formation [ 36 ]. Although there are numerous data from in vivo, in vitro, and clinical studies, a unanimous conclusion on which coating is the right choice for a specific pathogen has not been reached.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy data were obtained in similar studies in which silicone and latex catheters were evaluated against P. mirabilis . Zwitterions can either repel or prevent pathogen colonization, biofilm formation, and encrustation ( Kanti et al., 2022 ).…”
Section: Anti-fouling Approachesmentioning
confidence: 99%
“…It reduces reactive intermediates by releasing nitric oxide (NO), which interferes with ribosomes, DNA, and the cell wall to inhibit bacterial replication, growth, and biofilm formation ( Siddiq and Darouiche, 2012 ; Thompson et al., 2016 ). Nitrofurazone-coated catheters were tested against a wide spectrum of bacterial pathogens and were found to inhibit the adherence of E. coli and E. faecalis for 3–5 days( Stensballe, 2007 ; Desai et al., 2010 ; Kanti et al., 2022 ). In addition, several other comparative studies showed that the nitrofurazone-impregnated silicone catheter reduced the viable count of E. faecalis and inhibited S. epidermidis and P. aeruginosa biofilms ( Table 3 ) ( Kart et al., 2017 ; Al-Qahtani et al., 2019 ).…”
Section: Antimicrobial Coatings and Impregnationmentioning
confidence: 99%
“…Kidney stones are hard crystalline mineralized material that varies in size and is formed in the kidney or urinary tract. The complex phenotype of kidney stone disease is caused by the interplay of several genes, in conjunction with dietary and environmental variables [7]. Another urinary problem, a cyst, is a fluid-filled sac in the kidneys [8], whereas tumors are abnormal growths with symptoms such as abdominal pain, blood in the urine, and unexplained weight loss [9].…”
Section: Introductionmentioning
confidence: 99%